The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/1413-7372189590015
|View full text |Cite
|
Sign up to set email alerts
|

Possibilidades de diálogos entre abordagens humanistas: escutando vivências de psicodramatistas e gestalt-terapeutas

Abstract: RESUMO.A diversidade de concepções presente na Psicologia Clínica torna as possibilidades de diálogo entre abordagens uma questão importante. Objetivou-se neste trabalho compreender a dinâmica de aproximações e afastamentos entre duas abordagens humanistas -a Gestalt-terapia e o Psicodrama -a partir da análise dos dados provenientes de entrevistas realizadas com profissionais das duas orientações. A Teoria Fundamentada nos Dados foi escolhida como método, na busca de produção teórica a partir do contato analít… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The broader study from which the category of "obstacles" is taken revealed that lived experi-ence in undergraduate classes, initial supervision relationships and difficulties encountered during later clinical practice influence the stand that professionals would later take with regard to integration (Vieira & Vandenberghe, 2014). Other research also has shown that strategic choices and territorial claims influence psychotherapy trainee's theoretical orientation development (Wolff & Auckenthaler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The broader study from which the category of "obstacles" is taken revealed that lived experi-ence in undergraduate classes, initial supervision relationships and difficulties encountered during later clinical practice influence the stand that professionals would later take with regard to integration (Vieira & Vandenberghe, 2014). Other research also has shown that strategic choices and territorial claims influence psychotherapy trainee's theoretical orientation development (Wolff & Auckenthaler, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The word drama comes from Greek and has the same meaning as action, activity, and movement (Litwińska-Rączka, 2018). Psychodrama was developed by the psychiatrist Jacob Levy Moreno at the beginning of the 20th century (Apter, 2003; Vieira & Vandenberghe, 2014), as a result of his dissatisfaction with the shortcomings of scientific models at the time, which were seen as limiting of human expression and creativity (Almeida, 2006). Considered the first form of body psychotherapy, psychodrama does not exclusively use verbal expression (Carnabucci & Ciotola, 2013), and the complexities and roles of the patient are accepted without judgment, analysis, or interpretation (Apter, 2003).…”
Section: Psychodramamentioning
confidence: 99%
“…Moreno focused on a group psychotherapy approach in order to express the problem through dramatization (Soysal, 2021). Through the art of theater, Moreno sought the representation of problems (Vieira & Vandenberghe, 2014), by developing spontaneity (defined as the inner experience that allows the person to respond to the present moment through flexible behaviors and thoughts) (McVea et al, 2011), empathy and creativity (Oğuzhanoğlu & Özdel 2005).…”
Section: Psychodramamentioning
confidence: 99%
“…O Psicodrama é uma abordagem psicoterapêutica cuja importância para a Psicologia é indiscutível, uma vez que compreende o ser humano e seu desenvolvimento do ponto de vista relacional (Vieira & Vandenberghe, 2014). Para Alves (2011), o Psicodrama é visto como uma proposta de investigação do imaginário, de conflitos, do jogo de papéis e personagens que permeiam a convivência humana, tendo como objetivo o desenvolvimento da espontaneidade e a possibilidade de soluções criativas.…”
Section: Introductionunclassified